Pengaruh Dukungan Manajemen Puncak dan Kompleksitas Tugas Terhadap Kinerja Sistem Informasi Akuntansi pada PT. Varia Usaha Beton - Shafira Fawwaz Al Farraz; Wahyu Helmy Dimayanti Sukiswo (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The purpose of this study is to examine how work complexity and support from upper management affect the functionality of accounting information systems at PT Varia Usaha Beton. PT Varia Usaha Beton staff participated in this quantitative investigation. Direct distribution of questionnaires to PT Varia Usaha Beton staff members served as the method of data collection. Multiple linear regression was used for data analysis, and PLS software was used to handle the data.The findings showed that the effectiveness of PT Varia Usaha Beton's accounting information systems is positively and significantly impacted by top management assistance. Additionally, task complexity significantly improves the efficiency of PT Varia Usaha Beton's accounting information systems.